Determinants of Hypertension Among Farmers: A Literature Review - Afandi, Alfid; Kurniyawan, Enggal Hadi; Nur, Kholid Rosyidi Muhammad (Rajaki of Tulip Medika Publisher, 2026)
Hypertension among agricultural workers is a complex public health issue driven by a synergy of lifestyle choices, occupational hazards, and environmental exposures. Despite its prevalence, the specific interplay between farming-related risk factors and high blood pressure remains under-synthesized. This study aims to comprehensively analyze the key determinants ranging from sociodemographic to occupational factorsthat contribute to the risk of hypertension among farmers. A comprehensive literature review was conducted using ProQuest, Springer, and Science Direct databases. The search strategy utilized keywords such as “Hypertension,” “Farmers,” and “Blood Pressure.” Inclusion criteria focused on original research articles published between 2020 and 2025 that assessed risk factors in agricultural populations. A total of ten articles met the eligibility criteria and were analyzed. The review identified significant determinants categorized into occupational and behavioral factors. Key risk factors included age (>30 years), farming duration exceeding 8 years, and inadequate use of Personal Protective Equipment (PPE), suggesting a link to chemical exposure. Behavioral determinants included smoking, high sodium consumption, and psychological stress. Furthermore, the review highlights that non-pharmacological interventions, specifically health education and community-based promotion, effectively improve blood pressure control. Hypertension in farmers is associated with distinct occupational exposures (duration of work, PPE non-compliance) alongside traditional lifestyle risks. An integrated preventive strategy combining occupational safety education with lifestyle modification programs is essential for sustainable health management in agricultural communities.